Influence of long-period filter cut-off on elastic spectral displacements. - Akkar, Sinan
The effect of the long-period filter cut-off, Tc, on elastic spectral displacements is investigated using a strong ground-motion database from Europe and the Middle East. The relation between the filter and oscillator responses is considered to observe the influence of Tc for both analogue and digital records, and the variations with site classification, magnitude, filter order and viscous damping. Robust statistics are derived using the re-processed European data to generalize the effects of the long-period filter cut-off on maximum oscillator deformation demands as a function of these seismological and structural features. Statistics with a 95% confidence interval are derived to suggest usable period ranges for spectral displacement computations as a function of Tc. The results indicate that the maximum period at which spectral displacements can be confidently calculated depend strongly on the site class, magnitude and filter order. The period range where reliable long-period information can be extracted from digital accelerograms is twice that of analogue records.
Keywords: Data processing; Long-period filter cut-off.; Elastic oscillator displacement demands; European ground-motion database